Long-term survival in a large cohort of patients with venous thrombosis: incidence and predictors. - Linda E Flinterman; Astrid van Hylckama Vlieg; Suzanne C Cannegieter; Frits R Rosendaal (PLoS Medicine)
Background Venous thrombosis is a common disease with a high mortality rate shortly after the event. However, details on long-term mortality in these patients are lacking. The aim of this study was to determine long-term mortality in a large cohort of patients with venous thrombosis. Methods and findings 4,947 patients from the Multiple Environmental and Genetic Assessment study of risk factors for venous thrombosis (MEGA study) with a first nonfatal venous thrombosis or pulmonary embolism and 6,154 control individuals without venous thrombosis, aged 18 to 70 years, were followed up for 8 years. Death and causes of death were retrieved from the Dutch death registration. Standardized mortality ratios (SMRs) were calculated for patients compared with control individuals. Several subgroups were studied as well. 736 participants (601 patients and 135 controls) died over a follow-up of 54,948 person-years. The overall mortality rate was 22.7 per 1,000 person-years (95% CI 21.0-24.6) for patients and 4.7 per 1,000 person-years (95% CI 4.0-5.6) for controls. Patients with venous thrombosis had a 4.0-fold (95% CI 3.7-4.3) increased risk of death compared with controls. The risk remained increased up to 8 years after the thrombotic event, even when no additional comorbidities were present. The highest risk of death was found for patients with additional malignancies (SMR 5.5, 95% CI 5.0-6.1). Main causes of death were diseases of the circulatory system, venous thrombosis, and malignancies. Main limitation was a maximum age of 70 at time of inclusion for the first event. Therefore results can not be generalized to those in the highest age categories. Conclusions Patients who experienced a first venous thrombosis had an increased risk of death which lasted up to 8 years after the event, even when no comorbidities were present at time of thrombosis. Future long-term clinical follow-up could be beneficial in these patients. Please see later in the article for the Editors' Summary.